Interferences between surveillance/supervision and integrity (Academic Journal of Internal Affairs, 2022)
Aim: In the National Anti-Corruption Strategy (2020-2022) issued in 2020, the Government declared zero tolerance for corruption. This complex value-based anti-corruption approach places great emphasis on several approaches. These are, public service in accordance with the law, upholding the progress that has been achieved in combating corruption so far, strengthening resilience to corruption, and the development of individual and organizational integrity as well.Methodology: However, the combined use of anti-corruption and integrity-focused tools can also lead to the emergence of interference that greatly degrades the effects of different tools in combination with each other. These interactions can not only reduce the results of individually effective methods, but also make it difficult to interpret the real results of combined approaches and to plan further actions.Findings: The present paper, as a thought experiment, would like to draw attention to the phenomenon by presenting five such possible interference effects. It presents surveillance measures that result in decreased intrinsic motivation and the possibility of a temporary change in behavior; the dangers of undifferentiated use of inadequate methods for organizations and individuals; the secrecy of the reasons behind law-abiding behavior; the negative emotional effects of strong supervision; and possible anomalies in training development as well as draws attention to the importance of further empirical research on the issue. The combined use of different tools of a complex, value-based anti-corruption approach is now inevitable, and the targeted and differentiated use of different methods contributes greatly to the common social goal of curbing corruption and strengthening organizational and individual integrity. However, recognizing and taking steps to eliminate efficiency-reducing interferences between commonly used methods may be a cardinal question for success.Value: The key to the success of anti-corruption action is the structured analysis of existing law enforcement efforts, effective evaluation of results and systemwide planning.
Keywords: supervision; surveillance; compliance; integrity